Preparation method of high-rigidity PP hollow grid plate based on dolomite grading enhancement

By using multi-stage inorganic powder-grade matching filler and PP resin in the preparation process of PP hollow lattice board, and using microwave heating and vibration compaction treatment, the problem of insufficient performance of traditional PP hollow lattice board is solved, and a high-performance and low-cost preparation of PP hollow lattice board is achieved.

CN119613855APending Publication Date: 2025-03-14GUANGXI ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411575584.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

During the preparation process of traditional PP hollow lattice board, the production of organic volatile gases and the decrease in corona value caused by insufficient box bearing capacity, excessive low-quality waxes in the formula, which limits its application and development.

Method used

Multi-stage inorganic powder (dolomite, calcium carbonate, talc) graded filler is blended with PP resin, and is compacted by microwave heating and vibration to optimize the grading and interface characteristics of the filler, and improve the mechanical properties and heat resistance of the material.

Benefits of technology

It significantly improves the mechanical strength, thermal stability and overall performance of PP hollow lattice boards, reduces production costs, and meets the needs of high-performance and low-cost PP hollow lattice boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-rigidity PP hollow grid plate based on dolomite grading enhancement, which comprises the following steps: based on the design of multistage inorganic powder grading filler, taking dolomite powder, calcium carbonate and talcum powder, stirring and premixing to obtain a premix, then adding ionic liquid, and heating by stirring type microwave equipment to obtain the high-rigidity PP hollow grid plate based on dolomite grading enhancement. Then adding a surfactant and an organic oligomer, and continuing to stir and react to obtain a surface activated and modified graded filler; the preparation method comprises the following steps: stirring and blending the graded filler and PP resin to obtain a blended material, and then adding the blended material into a closed rubber mixing mill for pre-plasticizing treatment to obtain a mixture melt; the mixture melt is subjected to vibration compaction treatment and then plasticized and granulated again, plastic master batches are obtained, the plastic master batches and PP resin are taken to be mixed and then subjected to melt extrusion, and the hollow grid plate is obtained through mold forming. The invention aims to solve the problems in the traditional PP hollow grid plate preparation process and improve the comprehensive performance of the hollow grid plate by optimizing the grading of the filler and regulating and controlling the interface characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer material processing, and in particular relates to a method for preparing a high-rigidity PP hollow lattice plate based on dolomite gradation reinforcement. Background Art

[0002] As a lightweight and high-strength board, PP hollow grid board has excellent heat insulation, sound insulation, shock absorption and other properties due to its unique structure (central cavity), and is widely used in packaging, logistics, construction and other fields. However, there are some problems in the preparation process of traditional PP hollow grid board, such as 1) insufficient box bearing capacity, insufficient empty box pressure resistance, insufficient box strength and hardness, and bottom drag problem when carrying heavy objects; 2) the formula contains too much polyethylene wax and other low-quality waxes (especially small molecule waxes), resulting in a large amount of organic volatile gases (VOCs) generated during the board production process and the corona value of the board drops sharply over time, resulting in unstable printing, etc. These problems limit its further application and development.

[0003] In recent years, modification by adding heterogeneous fillers to polymer matrices has become an important means to improve the performance of polymer materials. Among the many fillers, natural mineral powders such as calcium carbonate, talc, dolomite, etc. are widely used in the modification of polymer materials due to their abundant resources, low prices, and environmental friendliness. Traditionally, single inorganic powders are widely used in the modification of PP hollow grid boards, each of which has unique physical and chemical properties, such as high filling properties of calcium carbonate, lubricity of talc, enhanced rigidity, and heat resistance of dolomite. However, the application of these single powders is often limited by their performance shortcomings, and it is difficult to fully meet the needs of high-performance PP hollow grid boards. Summary of the invention

[0004] In view of the above-mentioned shortcomings, the present invention discloses a method for preparing a high-rigidity PP hollow grid plate based on dolomite grading reinforcement. By optimizing the grading of the filler and regulating the interface properties, the present invention aims to solve the problems existing in the preparation process of the traditional PP hollow grid plate, improve the comprehensive performance of the hollow grid plate, and reduce the production cost at the same time, so as to meet the market demand for high-performance and low-cost PP hollow grid plates.

[0005] The present invention is achieved by adopting the following technical solutions: A method for preparing a high-rigidity PP hollow grid plate based on dolomite gradation reinforcement comprises the following steps: (1) Design of graded filler based on multi-level inorganic powder: dolomite powder, calcium carbonate and talcum powder are added to a stirring microwave device and stirred and premixed for 3 to 5 minutes to obtain a premix, then an ionic liquid is added and heated to 115 to 135°C and then kept constant temperature, and then a surfactant and an organic oligomer are added and stirred and reacted for 5 to 10 minutes to obtain a graded filler modified by surface activation; The mass ratio of dolomite powder, calcium carbonate and talc is (40-60): (32-48): (8-12); The particle size of the dolomite powder is 600-2000 mesh; The calcium carbonate is any one or more combinations of light calcium carbonate, heavy calcium carbonate and nano calcium carbonate, the particle size of the light calcium carbonate is 800-2000 mesh, the particle size of the heavy calcium carbonate is 600-1250 mesh, and the particle size of the nano calcium carbonate is 20-200nm; The particle size of the talcum powder is 3000-8000 mesh; The amount of the surfactant is 0.1 to 0.4 wt % of the premix; the amount of the organic oligomer is 0.1 to 0.8 wt % of the premix; (2) taking the graded filler obtained in step (1) and the PP resin and stirring and blending them at a speed of 1500 r / min for 5 minutes to obtain a blend, wherein the mass ratio of the graded filler to the PP resin is (80-85):(15-20), and then adding the blend into a closed rubber mixer for pre-plasticization to obtain a mixed material melt; (3) adding the mixed material melt obtained in step (2) to a vibrating compacting platform and treating it at 200-220° C. to obtain a dense melt; adding the dense melt to a single screw extruder for plasticization and granulation again to obtain a plastic masterbatch, wherein the single screw extruder includes the following working conditions: a temperature range of 145° C., 145° C., 150° C., 150° C., 150° C., 160° C., 160° C., 160° C., 160° C., 175° C., 185° C., an extrusion speed of 150 rpm, a melt flow rate of 50 L / min, an air-cooled hot cut of 5.0 Hz, and a host current of 35.7 A; (4) The plastic masterbatch obtained in step (3) and the PP resin are stirred and blended, and then added into a twin-screw extruder for melt extrusion and molded into a hollow grid plate through a mold, wherein the twin-screw extruder has the following working conditions: a temperature range of 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 215°C, 210°C, and a rotation speed of 400-550 r / min; after the hollow grid plate is cooled, it is fed into an automatic shearing machine through a traction machine for cutting to obtain products of different specifications and sizes.

[0006] Furthermore, the stirring speed in step (1) is 500 to 2000 r / min.

[0007] Furthermore, the ionic liquid in step (1) is any one or more combinations of imidazoles, pyridines, quaternary ammoniums, quaternary phosphoniums, pyrrolidines, piperidines and functionalized ionic liquids; and the amount of the ionic liquid is 0.5 to 0.7 wt % of the premix.

[0008] Furthermore, in step (1), the surfactant is any one or more combinations of stearic acid and stearate; and the organic oligomer is any one or more combinations of random polypropylene, polyethylene wax and bisphenol A epoxy resin.

[0009] Furthermore, during the pre-plasticization process in step (2), the material melting temperature is controlled at 200-220° C., the rotation speed is 450 r / min, and the feeding speed is 7 r / min.

[0010] Furthermore, in step (3), the vibration compaction platform has shear vibration and pressure vibration functions, and the vibration field parameters are: vibration frequency of 1 to 5 Hz, and amplitude of 1 to 3 mm.

[0011] Furthermore, the mass ratio of the plastic masterbatch and the PP resin in step (4) is (60-80):(20-40).

[0012] Furthermore, in step (4), the plastic masterbatch and the PP resin are stirred and blended at a speed of 600 to 800 r / min.

[0013] Furthermore, in step (4), the hollow lattice plate is placed on a cooling table for cooling, the cooling temperature of the cooling table is 30 to 40° C., and the cooling time is 2 to 3 minutes.

[0014] Compared with the prior art, this technical solution has the following beneficial effects: 1. The present invention introduces modified ultrafine talc powder and dolomite powder into the formula of calcium carbonate-filled PP hollow lattice plate. On the one hand, the talc powder / calcium carbonate ratio is used to improve the mechanical properties of the material while replacing small molecule lubricants such as polyethylene wax. On the other hand, the dolomite powder / calcium carbonate ratio is used to reduce the production cost of the material while improving the heat resistance of the PP hollow lattice plate.

[0015] 2. The present invention abandons the limitation of traditional single calcium carbonate powder filling PP hollow lattice plate, and adopts a compounding strategy of multi-level inorganic powder (including calcium carbonate, talc and dolomite), which not only gives full play to the high filling efficiency of calcium carbonate, but also cleverly combines the excellent lubricity and rigidity enhancement properties of talc and the excellent heat resistance of dolomite. This multi-component synergistic effect not only effectively reduces the use of small molecule lubricants, but also significantly improves the mechanical strength and thermal stability of PP hollow lattice plate, opening up a new way for the comprehensive upgrading of material performance.

[0016] 3. Through a carefully designed grading scheme, the present invention achieves an optimized combination of multi-level inorganic powders to ensure that the filler system has an ideal density, which not only increases the filling amount of powder in the PP matrix, achieves a higher proportion of inorganic reinforcement phase addition, but also significantly enhances the overall mechanical properties of the PP hollow grid plate, such as compressive strength, stiffness, etc. At the same time, this efficient filling strategy also helps to reduce production costs, improve the cost-effectiveness of products, and provide an economically feasible solution for industrial production.

[0017] 4. In traditional heat conduction heating, heat is gradually transferred from the outside to the inside of the inorganic powder, and it takes a long time for the material to be heated evenly. This heating method is inefficient and easily produces a temperature gradient inside the material, resulting in uneven heating. Compared with traditional coupling agents, the ionic liquid used in the present invention is a new type of environmentally friendly solvent with a low melting point, low vapor pressure and good hydrogen bond receptors, and is sensitive to microwaves. Ionic liquids absorb incident microwaves, induce atomic-scale dipole rotation, and transfer energy to inorganic powders through short-range conduction. Compared with traditional heating methods, the microwave heating used in the present invention vibrates rapidly under the action of a high-frequency electromagnetic field to generate heat, thereby heating the material inside and outside at the same time, without the need for heat conduction, so that the heating speed is fast and uniform, greatly improving production efficiency and saving energy.

[0018] 5. Using the traditional process of mixing + extrusion, it is difficult to achieve filler grading characteristics for fillers with multi-level powders and multi-peak distribution of particle size. The present invention innovatively adds a vibration compaction device in the granulation process, which can destroy the agglomeration structure between nanoparticles or other tiny particles to achieve effective dispersion. As the vibration frequency and displacement amplitude increase, the apparent viscosity of the polymer melt can be reduced, which promotes the graded filler to achieve the expected density and improves the density of the material. DETAILED DESCRIPTION

[0019] The present invention is further described by the following examples, but is not intended to be limiting of the present invention. Specific experimental conditions and methods not specified in the following examples are conventional methods commonly known to those skilled in the art.

[0020] Example 1: A method for preparing a high-rigidity PP hollow grid plate based on dolomite gradation reinforcement, comprising the following steps: (1) Dolomite powder, calcium carbonate and talc were added to a stirring microwave device and stirred for 4 minutes at a speed of 1000 r / min to obtain a premix, then an ionic liquid was added and heated to 125°C and kept constant temperature, and then a surfactant and an organic oligomer were added and stirred for 8 minutes to obtain a surface-activated modified graded filler; The mass ratio of dolomite powder, calcium carbonate and talc is 50:40:10; The particle size of the dolomite powder is 1200 mesh; The calcium carbonate is a combination of light calcium carbonate and nano calcium carbonate, the particle size of the light calcium carbonate is 1200 mesh, and the particle size of the nano calcium carbonate is 50 nm; The particle size of the talcum powder is 5000 mesh; The surfactant is stearic acid; the organic oligomer is polyethylene wax; the amount of the surfactant is 0.3wt% of the premix; the amount of the organic oligomer is 0.6wt% of the premix; The ionic liquid is imidazole; the amount of the ionic liquid is 0.6wt% of the premix; (2) The graded filler and PP resin obtained in step (1) are stirred and blended at a speed of 1500 r / min for 5 minutes to obtain a blend, wherein the mass ratio of the graded filler to the PP resin is 82:18, and then the blend is added to a closed rubber mixer for pre-plasticization to obtain a mixed material melt; During the pre-plasticization process, the material melt temperature is controlled at 210°C, the rotation speed is 450r / min, and the feeding speed is 7r / min; (3) adding the mixed material melt obtained in step (2) to a vibrating compacting platform and treating it at 210° C. to obtain a dense melt; adding the dense melt to a single screw extruder for plasticizing and granulating again to obtain a plastic masterbatch, wherein the single screw extruder includes the following working conditions: a temperature range of 145° C., 145° C., 150° C., 150° C., 150° C., 160° C., 160° C., 160° C., 160° C., 175° C., 185° C., an extrusion speed of 150 rpm, a melt flow rate of 50 L / min, an air-cooled hot cut of 5.0 Hz, and a host current of 35.7 A; The vibration compaction platform has shear vibration and pressure vibration functions, and the vibration field parameters are: vibration frequency is 3 Hz, amplitude is 2 mm; (4) The plastic masterbatch obtained in step (3) and the PP resin are stirred and blended at a speed of 700 r / min, and then added to a twin-screw extruder for melt extrusion and molded into a hollow grid plate through a mold, wherein the twin-screw extruder has the following working conditions: a temperature range of 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 215°C, 210°C, and a rotation speed of 500 r / min; the hollow grid plate is placed on a cooling table for cooling, the cooling temperature of the cooling table is 35°C, the cooling time is 3 min, and then the hollow grid plate is fed into an automatic shearing machine through a traction machine for cutting to obtain products of different specifications and sizes; the mass ratio of the plastic masterbatch to the PP resin is 70:30.

[0021] Embodiment 2: A method for preparing a high-rigidity PP hollow grid plate based on dolomite gradation reinforcement, comprising the following steps: (1) Dolomite powder, calcium carbonate and talc were added to a stirring microwave device and stirred at a speed of 500 r / min for 5 minutes to obtain a premix, then an ionic liquid was added and heated to 115°C and kept constant temperature, and then a surfactant and an organic oligomer were added and stirred and reacted for 10 minutes to obtain a surface-activated modified graded filler; The mass ratio of dolomite powder, calcium carbonate and talc is 40:32:8; The particle size of the dolomite powder is 600 mesh; The calcium carbonate is heavy calcium carbonate, and the particle size of the heavy calcium carbonate is 1000 mesh; The particle size of the talcum powder is 3000 mesh; The surfactant is stearate; the organic oligomer is a combination of random polypropylene and polyethylene wax; the amount of the surfactant is 0.1wt% of the premix; the amount of the organic oligomer is 0.1wt% of the premix; The ionic liquid is a quaternary ammonium; the amount of the ionic liquid is 0.5wt% of the premix; (2) The graded filler and PP resin obtained in step (1) are stirred and blended at a speed of 1500 r / min for 5 min to obtain a blend, wherein the mass ratio of the graded filler to the PP resin is 80:15, and then the blend is added to a closed rubber mixer for pre-plasticization to obtain a mixed material melt; During the pre-plasticization process, the material melting temperature is controlled at 200°C, the rotation speed is 450r / min, and the feeding speed is 7r / min; (3) adding the mixed material melt obtained in step (2) to a vibrating compacting platform and treating it at 200° C. to obtain a dense melt; adding the dense melt to a single-screw extruder for plasticizing and granulating again to obtain a plastic masterbatch, wherein the single-screw extruder has the following working conditions: a temperature range of 145° C., 145° C., 150° C., 150° C., 150° C., 160° C., 160° C., 160° C., 160° C., 175° C., 185° C., an extrusion speed of 150 rpm, a melt flow rate of 50 L / min, an air-cooled hot cut of 5.0 Hz, and a host current of 35.7 A; The vibration field parameters of the vibration compaction platform are: vibration frequency of 1 Hz, amplitude of 1 mm; (4) The plastic masterbatch obtained in step (3) and the PP resin are stirred and blended at a speed of 600 r / min, and then added to a twin-screw extruder for melt extrusion and molded into a hollow grid plate through a mold, wherein the twin-screw extruder has the following working conditions: a temperature range of 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 215°C, 210°C, and a rotation speed of 400 r / min; the hollow grid plate is placed on a cooling table for cooling, the cooling temperature of the cooling table is 30°C, the cooling time is 2 min, and then the hollow grid plate is fed into an automatic shearing machine through a traction machine for cutting to obtain products of different specifications and sizes; the mass ratio of the plastic masterbatch to the PP resin is 60:20.

[0022] Embodiment 3: A method for preparing a high-rigidity PP hollow grid plate based on dolomite gradation reinforcement, comprising the following steps: (1) dolomite powder, calcium carbonate and talc are added to a stirring microwave device and stirred for premixing at a speed of 2000 r / min for 3 minutes to obtain a premix, then an ionic liquid is added and heated to 135°C and then the temperature is kept constant, and then a surfactant and an organic oligomer are added and stirred for reaction for 5 to 10 minutes to obtain a surface activated modified graded filler; The mass ratio of dolomite powder, calcium carbonate and talc is 60:48:12; The particle size of the dolomite powder is 2000 mesh; The calcium carbonate is a combination of light calcium carbonate, heavy calcium carbonate and nano calcium carbonate, the particle size of the light calcium carbonate is 2000 mesh, the particle size of the heavy calcium carbonate is 1250 mesh, and the particle size of the nano calcium carbonate is 200nm; The particle size of the talcum powder is 8000 mesh; The surfactant is a combination of stearic acid and stearate; the organic oligomer is polyethylene wax; the amount of the surfactant is 0.4wt% of the premix; the amount of the organic oligomer is 0.8wt% of the premix; The ionic liquid is a combination of quaternary ammonium and pyrrolidine ionic liquids; the amount of the ionic liquid is 0.7wt% of the premix; (2) The graded filler and PP resin obtained in step (1) are stirred and blended at a speed of 1500 r / min for 5 minutes to obtain a blend, wherein the mass ratio of the graded filler to the PP resin is 85:20, and then the blend is added to a closed rubber mixer for pre-plasticization to obtain a mixed material melt; During the pre-plasticization process, the material melting temperature is controlled at 220°C, the rotation speed is 450r / min, and the feeding speed is 7r / min; (3) adding the mixed material melt obtained in step (2) to a vibrating compacting platform and treating it at 220° C. to obtain a dense melt; adding the dense melt to a single-screw extruder for plasticization and granulation again to obtain a plastic masterbatch, wherein the single-screw extruder includes the following working conditions: a temperature range of 145° C., 145° C., 150° C., 150° C., 150° C., 160° C., 160° C., 160° C., 160° C., 175° C., 185° C., an extrusion speed of 150 rpm, a melt flow rate of 50 L / min, an air-cooled hot cut of 5.0 Hz, and a host current of 35.7 A; The vibration field parameters of the vibration compaction platform are: vibration frequency of 5 Hz, amplitude of 3 mm; (4) The plastic masterbatch and PP resin obtained in step (3) are stirred and blended at a speed of 800 r / min, and then added to a twin-screw extruder for melt extrusion and molded into a hollow grid plate through a mold, wherein the twin-screw extruder has the following working conditions: a temperature range of 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 215°C, 210°C, and a rotation speed of 550 r / min; the hollow grid plate is placed on a cooling table for cooling, the cooling temperature of the cooling table is 40°C, the cooling time is 3 min, and then the hollow grid plate is fed into an automatic shearing machine through a traction machine for cutting to obtain products of different specifications and sizes; the mass ratio of the plastic masterbatch and the PP resin is 80:40.

[0023] Comparative Example 1: The method for preparing the PP hollow lattice plate described in this comparative example is different from the method described in Example 1 only in that a single calcium carbonate or dolomite is used in step (2) to mix with the PP resin to prepare the blend.

[0024] Comparative Example 2: The method for preparing the PP hollow lattice plate described in this comparative example is different from the method described in Example 2 only in that a single calcium carbonate or dolomite is mixed with the PP resin to prepare the blend in step (2).

[0025] Comparative Example 3: The method for preparing the PP hollow lattice plate described in this comparative example is different from the method described in Example 3 only in that in step (2), a single calcium carbonate or dolomite is used to mix with the PP resin to prepare the blend.

[0026] Experimental Example: Hollow grid plates and hollow grid plate boxes of different specifications and models were prepared according to the methods described in Examples 1 to 3 and Comparative Examples 1 to 3, and then their performances were tested. The test results are shown in Table 1.

[0027] Table 1 Test results of hollow grid panels and hollow grid box prepared by different methods

[0028] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a high-rigidity PP hollow grid plate based on dolomite gradation reinforcement, characterized in that: The following steps are involved: (1) Design of graded filler based on multi-level inorganic powder: dolomite powder, calcium carbonate and talcum powder are added to a stirring microwave device and stirred and premixed for 3 to 5 minutes to obtain a premix, then an ionic liquid is added and heated to 115 to 135°C and then kept constant temperature, and then a surfactant and an organic oligomer are added and stirred and reacted for 5 to 10 minutes to obtain a graded filler modified by surface activation; The mass ratio of dolomite powder, calcium carbonate and talc is (40-60): (32-48): (8-12); The particle size of the dolomite powder is 600-2000 mesh; The calcium carbonate is any one or more combinations of light calcium carbonate, heavy calcium carbonate and nano calcium carbonate, the particle size of the light calcium carbonate is 800-2000 mesh, the particle size of the heavy calcium carbonate is 600-1250 mesh, and the particle size of the nano calcium carbonate is 20-200nm; The particle size of the talcum powder is 3000-8000 mesh; The amount of the surfactant is 0.1 to 0.4 wt % of the premix; the amount of the organic oligomer is 0.1 to 0.8 wt % of the premix; (2) taking the graded filler obtained in step (1) and the PP resin and stirring and blending them at a speed of 1500 r / min for 5 minutes to obtain a blend, wherein the mass ratio of the graded filler to the PP resin is (80-85):(15-20), and then adding the blend into a closed rubber mixer for pre-plasticization to obtain a mixed material melt; (3) adding the mixed material melt obtained in step (2) to a vibrating compacting platform and treating it at 200-220° C. to obtain a dense melt; adding the dense melt to a single screw extruder for plasticization and granulation again to obtain a plastic masterbatch, wherein the single screw extruder includes the following working conditions: a temperature range of 145° C., 145° C., 150° C., 150° C., 150° C., 160° C., 160° C., 160° C., 160° C., 175° C., 185° C., an extrusion speed of 150 rpm, a melt flow rate of 50 L / min, an air-cooled hot cut of 5.0 Hz, and a host current of 35.7 A; (4) The plastic masterbatch obtained in step (3) and the PP resin are stirred and blended, and then added into a twin-screw extruder for melt extrusion and molded into a hollow grid plate through a mold, wherein the twin-screw extruder has the following working conditions: a temperature range of 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 215°C, 210°C, and a rotation speed of 400-550 r / min; after the hollow grid plate is cooled, it is fed into an automatic shearing machine through a traction machine for cutting to obtain products of different specifications and sizes.

2. The method for preparing high-rigidity PP hollow grid plate based on dolomite gradation reinforcement according to claim 1, characterized in that: The stirring speed in step (1) is 500-2000 r / min.

3. The method for preparing high-rigidity PP hollow grid plate based on dolomite gradation reinforcement according to claim 1, characterized in that: The ionic liquid in step (1) is any one or more combinations of imidazoles, pyridines, quaternary ammoniums, quaternary phosphoniums, pyrrolidines, piperidines and functionalized ionic liquids; the amount of the ionic liquid is 0.5-0.7wt% of the premix.

4. The method for preparing high-rigidity PP hollow grid plate based on dolomite gradation reinforcement according to claim 1, characterized in that: In step (1), the surfactant is any one or more combinations of stearic acid and stearate; the organic oligomer is any one or more combinations of random polypropylene, polyethylene wax and bisphenol A epoxy resin.

5. The method for preparing high-rigidity PP hollow grid plate based on dolomite gradation reinforcement according to claim 1, characterized in that: During the pre-plasticization process in step (2), the material melt temperature is controlled at 200-220°C, the rotation speed is 450r / min, and the feeding speed is 7r / min.

6. The method for preparing high-rigidity PP hollow grid plate based on dolomite gradation reinforcement according to claim 1, characterized in that: In step (3), the vibration field parameters of the vibration compaction platform are: vibration frequency of 1 to 5 Hz, and amplitude of 1 to 3 mm.

7. The method for preparing high-rigidity PP hollow grid plate based on dolomite gradation reinforcement according to claim 1, characterized in that: The mass ratio of the plastic masterbatch and the PP resin in step (4) is (60-80):(20-40).

8. The method for preparing high-rigidity PP hollow grid plate based on dolomite gradation reinforcement according to claim 1, characterized in that: In step (4), the plastic masterbatch and the PP resin are stirred and blended at a speed of 600 to 800 r / min.

9. The method for preparing high-rigidity PP hollow grid plate based on dolomite gradation reinforcement according to claim 1, characterized in that: In step (4), the hollow lattice plate is placed on a cooling table for cooling, the cooling temperature of the cooling table is 30 to 40° C., and the cooling time is 2 to 3 minutes.